VIEWS OF ISLAMIC ECONOMICS ON BUYING AND SELLING INTERESTS THROUGH THE SHOPEE KAJEN ONLINE SYSTEM - Neni Wulandari (AL-ITTIFAQ: Jurnal Ekonomi Syariah, 2023)
Buying and selling is an activity that is carried out by exchanging property or something desired based on a mutually binding agreement between the seller as the owner of the goods and the buyer as the party paying for the goods sold. The online shopee trading system is one of the buying and selling systems which is still trending today. This study aims to describe the description of the shopee application, describe the advantages and disadvantages of using the shopee application according to Islamic economics, describe buying and selling in online shopee marketplaces according to a review of Islamic business ethics, describing the impact of Islamic business ethics caused by online shopping at the Kajen shoppee. used qualitative approach method. Which of these research methods produces a descriptive description of the shopee application, the advantages and disadvantages of using the shopee application according to Islamic economics, buying and selling in online shopee marketplaces according to a review of Islamic business ethics the impact of Islamic business ethics caused by online shopping at the Kajen shoppee. The results of this study prove that by using the online shopee application it is easy and fast. By getting benefits, the marketing is expanding to the province and can also go abroad. Buy Online shopee However, sometimes time is constrained if you get a lot of orders (a lot) on buying and selling online keywords: Islamic economics, buying and selling, online shopee